2011
DOI: 10.1542/peds.2010-2037
|View full text |Cite
|
Sign up to set email alerts
|

Adults With Chronic Health Conditions Originating in Childhood: Inpatient Experience in Children's Hospitals

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Health care innovations have improved survival in children with conditions previously fatal in childhood. Implications for specific diseases have been reported, but little information is available on disease comparisons or population increases in adult survivors of childhood illness. WHAT THIS STUDY ADDS:In this study of adults with chronic childhood diseases treated at 30 children's hospitals over a 10-year period, 6 conditions were compared and patient population growth was proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 44 publications
4
107
0
3
Order By: Relevance
“…In addition, with the increasing number of adults with chronic health conditions originating in childhood who continue to receive care at children's hospitals, med-peds hospitalists will be essential in the provision of care and oversight to this population. 12 Our survey found that 25.1% of med-peds hospitalists included in the survey are already providing care for adults who are survivors of congenital or childhood disease.…”
Section: Statistical Methods and Data Analysismentioning
confidence: 82%
“…In addition, with the increasing number of adults with chronic health conditions originating in childhood who continue to receive care at children's hospitals, med-peds hospitalists will be essential in the provision of care and oversight to this population. 12 Our survey found that 25.1% of med-peds hospitalists included in the survey are already providing care for adults who are survivors of congenital or childhood disease.…”
Section: Statistical Methods and Data Analysismentioning
confidence: 82%
“…Patients of all ages, including patients aged ≥18 years, were included in this analysis because many young adults, especially those with chronic conditions originating in childhood, continue to receive inpatient care at children's hospitals. 22 …”
Section: Study Populationmentioning
confidence: 99%
“…hospitals 44 ) argues for planning and resources that enable sufficient staffing and expertise within PPC programs to ensure high-quality care for these adult patients and effective transition from pediatric to adult-oriented health care systems when appropriate.…”
Section: Figurementioning
confidence: 99%